Implementation of Merdeka Belajar Curriculum in Traditional Islamic Education Institutions: A Multisite Study on Dayah in Aceh Tamiang - Nasution, Taufik; Nasution, Wahyudin Nur; Hanum , Azizah (LP. Ma'arif Janggan Magetan, 2024)
This study aims to analyze the implementation of the Merdeka Learning Curriculum in two Islamic boarding schools in Aceh Tamiang District, namely Dayah Babul Huda and Dayah Ibdaul Islam. The study identifies the processes of curriculum planning, implementation, and evaluation, as well as the supporting factors and challenges faced. A multisite study with a qualitative approach was employed. The results show that both boarding schools implemented the Merdeka Learning Curriculum through collaboration between school leaders and teachers, with adjustments to Islamic values and local wisdom of Aceh. At Dayah Babul Huda, project-based learning and hands-on exploration were the main strategies, while Dayah Ibdaul Islam applied differentiated learning, grouping students based on their characteristics and interests. Evaluation was carried out periodically, focusing on formative and summative assessments. The findings imply that traditional Islamic education institutions are capable of adapting to modern educational reforms when local values are preserved and leadership is collaborative. This research contributes to the understanding of curriculum contextualization in conservative religious environments. Future studies are encouraged to explore long-term impacts of the Merdeka Learning Curriculum on student character development and to examine similar implementations in broader and more diverse Islamic educational settings